Find x :
tan-1 ( x-1 ) + tan-1x + tan-1 ( x+1 ) = tan-1 3x

tan-1(x+1+x-1 / 1-(x+1)(x-1)) = tan-1 3 + tan-1  x  ............when x2-1<3 and 3x<1
                               

solve it .......and u'll get (2x/2-x2 ) = (3-x/1+3x) when x lies between -√2 and 1/3
i.e. x+1(x2 -10x+6) = o when x lies b/w ......
so x = -1 neglecting x2 -10x+6 as its root does not belong to (-√2 , 1/3)
 
  • 1
isn't it plus or minus 1/2 ? o.O
  • 7
i am also getting x = -1 by calculating this.
 
  • 0
the right answer is plus minus 1/2 @ bhavya :) 
  • 3
yes,Sorry got it.


 
  • 72
3009
  • -3
Jjjjkkkl
  • 1
x=0 is also a solution. It's quite obvious by hit-and-trial.
  • 1
Here it is

  • -2
There will be three solutions
Just check it

Note : do not cut "x" because it variable, there can be more roots and any value of "x" would be possible if u cut "x". But u can cut "2" because it is constant

  • 14
Apni kat ke kha le
  • -2
The solution

  • 6
tan-¹3x
  • 0
What are you looking for?